DNA Polymerase Beta Participates in Mitochondrial DNA Repair - Sykora, P. (Mol Cell Biol, 2017)
We have detected DNA polymerase beta (Polβ), known as a key nuclear base excision repair (BER) protein, in mitochondrial protein extracts derived from mammalian tissue and cells. Manipulation of the N-terminal sequence affected the amount of Polβ in the mitochondria. Using Polβ fragments, mitochondrion-specific protein partners were identified, with the interactors functioning mainly in DNA maintenance and mitochondrial import. Of particular interest was the identification of the proteins TWINKLE, SSBP1, and TFAM, all of which are mitochondrion-specific DNA effectors and are known to function in the nucleoid. Polβ directly interacted functionally with the mitochondrial helicase TWINKLE. Human kidney cells with Polβ knockout (KO) had higher endogenous mitochondrial DNA (mtDNA) damage. Mitochondrial extracts derived from heterozygous Polβ mouse tissue and KO cells had lower nucleotide incorporation activity. Mouse-derived Polβ null fibroblasts had severely affected metabolic parameters. Indeed, gene knockout of Polβ caused mitochondrial dysfunction, including reduced membrane potential and mitochondrial content. We show that Polβ is a mitochondrial polymerase involved in mtDNA maintenance and is required for mitochondrial homeostasis.